Humanism Perspective in Differentiated Learning in Elementary Schools: Systematic Literature Review: Systematic Literature Review - Zurriyana Nainggolan; Inayatus Saadah Dalimunthe; Safril Abidin Hasibuan; Pahri Siregar (International Journal of Community Service (IJCS), 2026)
Differentiated learning emerges as a strategic response to the diversity of student characteristics in elementary schools, particularly within the framework of the Merdeka Curriculum in Indonesia. The humanistic perspective offers a relevant philosophical foundation because it places students at the center of the learning process and recognizes the uniqueness of each learner. This study aims to analyze how the humanistic perspective contributes to the implementation of differentiated learning in elementary schools through a Systematic Literature Review (SLR) approach. The study employs the SLR method following the PRISMA 2020 guidelines through systematic identification, screening, and synthesis of literature. Literature was searched in databases such as Google Scholar, SINTA, and reputable international journals within the publication range of 2010 to 2025. From 84 identified articles, 16 articles met the inclusion criteria and were further analyzed using thematic analysis. The findings indicate that the humanistic perspective, especially the theories of Abraham Maslow and Carl Rogers, provides essential philosophical foundations for differentiated learning by emphasizing self-actualization, freedom to learn, empathy, and the recognition of individual differences. The integration of humanistic principles strengthens the three dimensions of differentiation, namely content, process, and product, by ensuring that learning activities respond to students' readiness, interests, and learning profiles. Furthermore, the implementation of humanistic values ​​in differentiated learning enhances students' learning motivation, engagement, self-confidence, and holistic development. Therefore, the humanistic perspective plays a strategic role as a conceptual basis for designing meaningful, contextual, and learner centered differentiated instruction in elementary schools.